Медичний спа- та санаторно-курортний туризм: відмінність концепцій - Щука Галина; Scsuka Halina; Shchuka Halyna; Лемко Іван; Lemko Ivan; Шейко Віталій; Sheiko Vitalii (Видавничий дім «Гельветика», 2024)
Резюме. Санаторно-курортний туризм переживає кризу, яку намагається подолати шляхом диверсифікації та комерціалізації послуг, що поступово перетворює його у медичний спа-туризм. Мета дослідження – визначити наслідки цього процесу, встановивши спільне та відмінне у концепціях санаторно-курортного та медичного спа-туризму. Методологія дослідження: системно-структурний підхід, методи аналізу та синтезу, індукції та дедукції, прогнозування, аналогії, наукового узагальнення, співставлення та порівняння. Результати дослідження: визначено спільне, відмінне та індивідуальне у концепціях цих видів туризму. Практичне значення: виокремлено характерні риси, які відрізняють санаторно-курортний туризм від медичного спа-туризму, і можуть бути втрачені внаслідок злиття цих сегментів.

Abstract. It has been established that health-resort tourism is experiencing a crisis in most countries. One of the ways out of this crisis is diversification and commercialization of such services, which brings them closer to the segment of medical spa tourism and allows scientists to predict gradual confluence of these types of health tourism. The aim of the study: to determine the consequences of this process, determining common features and differences in the concepts of health-resort and medical spa tourism. The research methodology is based on a systemic-structural approach using methods of analysis and synthesis, induction and deduction, forecasting, analogy, scientific generalization, juxtaposition and comparison. Results of the study: common, different and individual in the concepts of health-resort tourism and medical spa tourism are defined. It has been established that sanatorium-resort tourism and the medical direction of spa tourism ensure that tourists receive medical services during the trip, and are regulated simultaneously by the legal norms of tourist activity and medical practice. However, these types of tourism differ in funding sources; the principles of formation of the stay program; requirements for the availability of natural healing resources and have different target audiences, occupying different segments of the tourist market. Practical significance: the obtained results allow us to clarify and outline concrete proposals in the development of each of the studied segments. Significance / originality: characteristic features that distinguish health-resort tourism and medical spa tourism are highlighted, and these peculiarities may be lost as a result of confluence of these segments. This information may serve as a promotion for reevaluation the reorganization processes of health-resort tourism.
Medical Spa & Health resort tourism: difference of concepts
Keywords: санаторно-курортний туризм; медичний спа-туризм; порівняння концепцій; health tourism